Mapping the climate impact of rye bread production in Sweden: insights into cultivation, packaging, and surplus management for sustainable food systems - Hildersten, S.; Bartek, L.; Brancoli, P.; Eriksson, M.; Karlsson Potter, H.; Strid, I. (Frontiers in Sustainable Food Systems, 2025)
The current food system contributes strongly to environmental pressure, with bread, a staple product in many countries, being consumed and wasted in substantial quantities. This study assessed the environmental impact of rye bread produced in Sweden using life cycle assessment (LCA), with the aim of identifying ways to reduce this impact. A unique aspect of this work was the independent collaboration between research and industry, which provided a highly representative description of the Swedish rye bread production and distribution system. The climate impact of rye bread was found to be 0.81 kg CO2eq per kg, with production of ingredients being the main hotspot for all impact categories assessed. In simulations of impact reduction pathways, the highest climate savings were found for prevention of surplus generated at bakery and retail, which reduced the climate impact by 8%. Using the standardised ReCiPe method, accounting for 18 midpoint impact categories and three damage indicators at endpoint, yielded vital insights into otherwise often overlooked environmental aspects of food production. By using data provided by an industry actor, the results from this study enabled in-depth mapping of the resources required to produce rye bread at industrial level in Sweden, providing unique insights into production. These results can act as an essential cornerstone for future research and development of sustainable food systems.